2006
DOI: 10.1111/j.1468-3083.2006.01666.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin problems after a tsunami

Abstract: Unhygienic conditions, exposure to a hazardous environment and contact with various objects during and after the tsunami probably increased the prevalence of infections-infestations, traumatic skin disorders and contact dermatitis. To prevent these problems and associated secondary bacterial infections, health-related education and early medical management are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 7 publications
(13 reference statements)
1
39
2
1
Order By: Relevance
“…Based on these results, in relation to eczema, the effect of disasters on the prevalence of eczema in the population as a whole, as well as in children with tsunami experience, cannot be excluded. After the earthquake in Sumatra in 2004, eczema was reportedly the second most prevalent symptom among dermatology patients (Lee et al 2006). After the Great East Japan Earthquake, wheeze and eczema were found in 22% and 55%, respectively, of children with food allergies (Yamaoka et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these results, in relation to eczema, the effect of disasters on the prevalence of eczema in the population as a whole, as well as in children with tsunami experience, cannot be excluded. After the earthquake in Sumatra in 2004, eczema was reportedly the second most prevalent symptom among dermatology patients (Lee et al 2006). After the Great East Japan Earthquake, wheeze and eczema were found in 22% and 55%, respectively, of children with food allergies (Yamaoka et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies after combination disasters involving both an earthquake and a tsunami have also been reported; these include skin problems such as eczema after the 2004 Sumatra earthquake (Lee et al 2006) and control of asthma after the 2011 Great East Japan Earthquake (Yamaoka et al 2011;Fukuhara et al 2012;Minoura et al 2012;Yanagimoto et al 2012;Ishiura et al 2013;Ohkouchi et al 2013). Although those studies were highly valuable, the generalizability of their results was limited as they relied primarily on data from patients; data from individuals who did not visit a clinic or medical institution remained hidden.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,14 Other dermatologic conditions associated with occupational and chemical exposures in postflooding cleanup activities have been documented. 2,4 We found that workers with a self-reported rash were 4 times more likely to be sleeping in huts that had sustained flooding at the time of rash onset. Similarly, those with papular urticaria were 20 times more likely to be sleeping in the previously flooded huts.…”
Section: Commentmentioning
confidence: 86%
“…2007;143(11): [1393][1394][1395][1396][1397][1398] O UTBREAKS OF DERMATOlogic diseases occur frequently after hurricanes and flooding 1,2 ; however, few of these outbreaks have been systematically investigated. 3,4 The causes of dermatologic problems after recent hurricanes in the United States have included staphylococcal infections, tinea corporis, and arthropod bites. 5 Hurricane…”
Section: Discussionmentioning
confidence: 99%